Coordinated active power reduction strategy for voltage rise mitigation in LV distribution network - Ainah, Priye (Department of Electrical Engineering, 2018)
Integration of renewable energy systems by the utility, customers, and the third party into the electric power system, most especially in the MV and LV distribution networks grew over the last decade due to the liberalization of the electricity market, rising energy demand, and increasing environmental concern. The distributed rooftop PV system contributes to relieve the overall load, reduce losses, avoid conventional generation upgrade, and better matching of demand on the LV distribution network. Originally, the LV distribution network is designed for unidirectional current flow, that is from the substation to customers. However, a high penetration of rooftop solar PVs (with power levels typically ranging from 1 – 10 kW) may lead to the current flowing in the reverse direction and this could result in a sudden voltage rise. These negative impacts on the network have discouraged the distribution network operators (DNOs) to allow increased PV penetration in the LV distribution network because some customers load, and equipment are sensitive to voltage perturbation. Presently, the most applied voltage rise mitigation strategy for high rooftop solar PV penetration is the total disconnect from the LV distribution network when the voltage at the point of common coupling (PCC) goes above statutory voltage limits. However, the sudden disconnection of the PV system from the grid can cause network perturbation and affect the security of the network. This action may also cause voltage instability in the network and can reduce the lifetime of grid equipment such as voltage regulators, air conditioner etc. Due to this negative impact, different voltage rise mitigation strategies such as the active transformer with on load tap changers (OLTC), distributed battery energy storage system and reactive power support (D-STATCOM, etc.) have been used to curtail voltage rise in the distribution network. However, the implementation of D-STATCOM device on a radial LV distribution network results in high line current and losses. This may be detrimental to the distribution network. Therefore, in this thesis, a coordinated active power reduction (CAPR) strategy is proposed using a modified PWM PI current control strategy to ramp down the output power and voltage of a grid-tied voltage source inverter (VSI). In the proposed strategy, a reactive reference is generated based on the measured voltage level at the PCC using a threshold voltage algorithm to regulate the amplitude of the modulating signal to increase the off time of the high frequency signal which shut down the PV array momentary in an extremely short time and allow the VSI to absorb some reactive power through the freewheeling diode and reduce voltage. The proposed CAPR strategy was designed and simulated on a scaled down simple radial LV distribution network in MATLAB®/Simulink® software environment. The results show that the CAPR can ramp down the PV output power, reduce reverse power flow and reduce the sudden voltage rise at the point of common coupling (PCC) within ±5% of the standard voltage limit. The study also compares the performance of the proposed CAPR strategy to that of the distributed static compensator (D-STATCOM) and battery energy storage system (BESS) with respect to response time to curtail sudden voltage rise, losses and reverse power flow. The investigation shows that the D-STATCOM has the faster response time to curtail voltage rise. However, the voltage rise reduction is accompanied by high current, losses and reverse active power flow. The introduction of the BESS demonstrates better performance than the D- STATCOM device in terms of reverse power flow and losses. The CAPR strategy performs better than both D-STATCOM and BESS in terms of line losses and reverse power flow reduction.